2006
DOI: 10.1176/ajp.2006.163.10.1739
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Patient-Therapist Relationship in Dynamic Psychotherapy: An Experimental Study of Transference Interpretations

Abstract: The authors could not show differences in average effectiveness between treatments. However, the moderator analyses indicated that treatment worked through different active ingredients for different patients. Contrary to common expectation, patients with poor object relations profited more from therapy with transference interpretations than from therapy with no transference interpretations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(60 citation statements)
references
References 29 publications
2
56
1
Order By: Relevance
“…The notions of transference and counter-transference (raising awareness of the therapeutic relationship) [32].…”
Section: Methodsmentioning
confidence: 99%
“…The notions of transference and counter-transference (raising awareness of the therapeutic relationship) [32].…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the First Experimental Study of Transference-interpretations [10, 17] was to measure the effects of Transference Work (TW) in dynamic psychotherapy. FEST was a randomized controlled trial where one hundred patients seeking psychotherapy for depression, anxiety, and personality disorders, where allocated to psychodynamic psychotherapy with low to moderate levels of TIs (the transference group; N  = 52) or psychodynamic psychotherapy with no TIs, only RI’s (the comparison group; N  = 48).…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to expectation, no significant between-group differences were revealed in FEST. Moderator analyses showed that patients with a life-long pattern of poor relational functioning measured with the QOR [17] and/or patients with personality disorders profited more in therapy with TI than without TI [10, 17, 26]. This was especially true for women, while men responded better to therapy without TI compared to women [11].…”
Section: Methodsmentioning
confidence: 99%
“…Such patterns are presumed to reflect enduring inner psychological representations of self-other relations. The QORS has been used in a number of studies, with consistently satisfactory levels of rater reliability (Høglend et al, 2006;Piper & Duncan, 1999) and concurrent validity (Lindfors, Knekt, Virtala, & Haaramo, 2013). The interviewer considers behavioral manifestations, affect regulation, self-esteem regulation, and historical antecedents in the assessment of QOR.…”
Section: Quality Of Object Relationsmentioning
confidence: 99%
“…Higher scores are reflective of more mature levels of object relations. The QORS has been used in a number of studies, with consistently satisfactory levels of rater reliability (Høglend et al, 2006;Piper & Duncan, 1999) and concurrent validity (Lindfors, Knekt, Virtala, & Haaramo, 2013). QORS interviews for the ETP were conducted by trained clinicians (n = 5) who did not provide treatment to the participants.…”
Section: Quality Of Object Relationsmentioning
confidence: 99%